2017
DOI: 10.1080/00913847.2017.1386069
|View full text |Cite
|
Sign up to set email alerts
|

The mental wellbeing of current and retired professional cricketers: an observational prospective cohort study

Abstract: Objective: Scientific knowledge about symptoms of common mental disorders in professional cricket is non-existent. Consequently, the aims of the study were to determine the prevalence and the 6 months incidence of symptoms of common mental disorders (CMD: distress, anxiety/depression, sleep disturbance, adverse alcohol use) among current and former professional cricketers and to explore the association of potential stressors (significant injury, surgery, adverse life events, career dissatisfaction) and CMD. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 39 publications
2
73
1
Order By: Relevance
“…From these, 54 studies were excluded for various reasons (not in English: n=1; not an original study: n=5; not including only current or former elite athletes: n=22; not presenting an adequate outcome measure: n=26). The reference check of the included studies resulted in three additional relevant studies 12–14. Consequently, our systematic review includes 34 original studies: 18 including exclusively current elite athletes,12 13 15–30 11 including exclusively former elite athletes31–41 and four including both current and former elite athletes 14 42–44.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From these, 54 studies were excluded for various reasons (not in English: n=1; not an original study: n=5; not including only current or former elite athletes: n=22; not presenting an adequate outcome measure: n=26). The reference check of the included studies resulted in three additional relevant studies 12–14. Consequently, our systematic review includes 34 original studies: 18 including exclusively current elite athletes,12 13 15–30 11 including exclusively former elite athletes31–41 and four including both current and former elite athletes 14 42–44.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our meta-analysis, we found that 19.6% (95%CI: 16.0 to 23.3) of elite athletes reported symptoms of distress (high between-study heterogeneity: Q=77.1, P<0.001, ^2=85.7%). Ten studies reported prevalence data on symptoms of sleep disturbance among 4782 elite athletes from various sports:12–16 21 23 29 43 44 meta-analysis revealed that 26.4% (95%CI: 21.6 to 31.2) of elite athletes reported symptoms of sleep disturbance (high between-study heterogeneity: Q=133.651, P<0.001, ^2=92.518%). Nine studies reported prevalence data on symptoms of anxiety/depression (not differentiated) among 2895 elite athletes from various sports:12–14 19 21 23 42–44 meta-analysis showed that 33.6% (95%CI: 27.4 to 39.7) of elite athletes reported symptoms of anxiety/depression (high between-study heterogeneity: Q=109.737, P<0.001, ^2=91.799%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from elite athletes experiencing distress highlights a tendency for some to conceal difficulties from coaching staff and teammates (Doherty, Hannigan, & Campbell, 2016). Additionally, elite athletes who engage in externalising coping strategies, such as problematic alcohol use (Gouttebarge et al, 2018;O'brien, Blackie, & Hunter, 2005;Schuring, Kerkhoffs, Gray, & Gouttebarge, 2017) may experience these coping responses as ineffective in the longer term, potentially enhancing psychological distress through cascading problems associated with heavy substance use.…”
Section: Introductionmentioning
confidence: 99%